2020
DOI: 10.1186/s12955-020-01519-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes mellitus and health-related quality of life among patients with chronic kidney disease: results from the Chinese Cohort Study of Chronic Kidney Disease (C-STRIDE)

Abstract: Background: The prevalence of diabetes mellitus (DM) among patients with chronic kidney disease (CKD) has been increasing in recent years in China. This study aimed to evaluate the association between DM and health-related quality of life (HRQOL) in patients with CKD. Methods: In our study, participants with CKD stage 1 to 4 from 39 centers in China were screened and enrolled. The Kidney Disease Quality of Life (KDQOL™-36) questionnaire was used to assess HRQOL. Participants were divided into a diabetic group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, a declining physical component score during the study period was more pronounced in those with more advanced CKD. Similarly, the presence of DM was significantly associated with lower HRQoL, particularly with lower physical function, in CKD patients [29]. Furthermore, in previous studies, poor physical quality of life was associated with a higher risk of mortality in patients with CKD or comorbid DM and CKD [26,30,31].…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, a declining physical component score during the study period was more pronounced in those with more advanced CKD. Similarly, the presence of DM was significantly associated with lower HRQoL, particularly with lower physical function, in CKD patients [29]. Furthermore, in previous studies, poor physical quality of life was associated with a higher risk of mortality in patients with CKD or comorbid DM and CKD [26,30,31].…”
Section: Discussionmentioning
confidence: 74%
“…Inconsistent with these results,(Chen et al, 2020) (11) recorded that DM was negatively correlated with HRQOL scores in both categories, but the magnitude and dimensions and of correlation were…”
Section: Ethical Considerationsmentioning
confidence: 89%
“…Evaluating health-related quality of life and associated variables in patients with Diabetic Nephropathy and DM is critical for guiding health education and suitable personalized treatment. (11,12) At the level of disease prevention, increasing public awareness about diabetes and its associated risk factors as obesity and lack of exercise is essential and can support current institutional efforts. This can be achieved through collaborative work from all stakeholders such as the ministry of health (MOH) and universities in several ways such as including the publication of small Arabic booklets in plain language, Discussions, lectures, etc (13,14) Finally, to combat the increasing prevalence of diabetes, there is now an urgent need for a long-term national plan focusing on prevention, education, and a multidisciplinary approach.…”
Section: The United States National Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Japanese patients with chronic kidney disease (CKD) reported a gradual decrease in quality-adjustment weight with the progression of the CKD, as measured by the EQ-5D [24]. A cross-sectional study has reported both diabetes and albuminuria to be negatively associated with PCS and MCS scores in patients with CKD [25]. In addition, a longitudinal study of men with diabetes and comorbid DN found that proteinuria at enrollment was negatively associated with PCS and MCS on the kidney disease QoL measure at 4-month follow-up [26].…”
Section: Discussionmentioning
confidence: 99%